Analysis of image-forming elements in the urban service center area of Pangkalpinang City - Nugraha, Rifqi Adi; Rambe, Aisyah Ronawan; Zuhdi, Ahmad; Putri, Diti Artanti Utami; Mujiburrakhman, Muhammad (Priviet Social Sciences Journal, 2025)
Pangkalpinang City is one of the municipalities in Indonesia that was planned to transform into a developed urban environment by 2030. To help achieve the city’s development goal, this study presents an analysis of the spatial structure of the urban service center of Pangkalpinang City, which comprises the Rawa Bangun, Gedung Nasional, Masjid Jamik, Pasar Padi, and Bintang sub-districts, using Kevin Lynch’s image-forming elements, that is, path, edge, district, node, and landmark. A qualitative descriptive method was used to interpret users’ spatial experiences through field observations and supporting secondary data. The results show that the urban service center area is shaped by a complex hierarchical path, natural and artificial edges, diverse functional districts, many nodes in the form of intersections, bridges, a public transport terminal, and ten cultural and non-cultural landmarks. These findings highlight how Pangkalpinang City’s spatial structure and functional patterns may interact to support the city’s public services, and they can guide future spatial planning of the city towards a more integrated and citizen-friendly city.